MicroRNA-92a is a circadian modulator of neuronal excitability in Drosophila - Xiao Chen (Nature Portfolio, 2017)
Accumulating evidence suggests that microRNAs play a role in circadian regulation. Here the authors show that in theDrosophila brain, mir-92a suppresses the excitability of PDF neurons—key circadian pacemaker cells in Drosophila—via inhibiting the translation of its target sirt2.